Nas veredas negras do sertão: histórias de vida familiar de escravizados no sertão brasileiro (Vila de Catolé do Rocha/Paraíba, 1836-1866) - Sousa, Anicleide de (2018)
This piece of research focuses on the enslaved population that lived in the Vila de Catolé do Rocha in the 19th century. The idea of researching this social group arose, initially, from the concerns and gaps still present in the Brazilian historiography about the hinterland region of the country, which for a long time provided little importance for this share of the population, silencing the history of enslaved women and men while making up the Brazilian hinterland society. By means of this dissertation, we surveyed the presence of captives in the Vila de Catolé do Rocha and we analyzed some of the experiences of enslaved women, children and men, focusing on their family bonds and spiritual kinship, both in relationships with individuals of their same condition and with free ones. This research is based on the theoretical and methodological framework of the Social History and the Historical Demography. Social History, whose assumption considers the enslaved population as historical individuals, and Historical Demography, which is based on census records with the use of statistical techniques, enabled quantitative analyses of ecclesiastical sources (baptism and marriage books) allied to intensive qualitative analysis of primary documents. Among the results, we highlight the resistance actions to the slave system, such as the establishment of parental relationships, the godparenthood, a spiritual alliance that allowed the formation of solidarity networks so as to survive in a hinterland slave society of the nineteenth century as well as the history of the freedom conquest by captive women and men based on official sources. Finally, this study is part of the research line regarding History and Regionalities, which are understood as historical constructs of symbolic and political character, components of the historical cultures produced, spread and appropriated by historically situated individuals, thus, the knowledge of the historical process, with emphasis on regional historicity, is an action scenario that allows the historians´ formation to have better knowledge of their realities and of the documentary collections. These processes are relevant to the construction of political cultures applied to citizenship and democracy, and to the renewal of history teaching in basic education and higher education, in order to enable a deepening in the field of history and historical culture.